2016
DOI: 10.1007/s10653-016-9888-z
|View full text |Cite
|
Sign up to set email alerts
|

Potentially harmful elements in house dust from Estarreja, Portugal: characterization and genotoxicity of the bioaccessible fraction

Abstract: Due to their behavioral characteristics, young children are vulnerable to the ingestion of indoor dust, often contaminated with chemicals that are potentially harmful. Exposure to potentially harmful elements (PHEs) is currently exacerbated by their widespread use in several industrial, agricultural, domestic and technological applications. PHEs cause adverse health effects on immune and nervous systems and can lead to cancer development via genotoxic mechanisms. The present study is an integrated approach tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 53 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…The Estarreja Chemical Complex (ECC), located near Aveiro, in the center region of Portugal, has had intense industrial activity since the early 1950s, and high environmental levels of potentially toxic elements such as arsenic (As) and mercury (Hg) have been reported at this region [32,33]. Despite the significant number of studies focusing on determining the severity and the extension of the contamination [34,35,36,37,38] only a few have tried to assess potential health effects on the resident population [39,40,41,42,43]. Hence, the area displays interesting characteristics to study the potential effect of long-term exposures to chemicals in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The Estarreja Chemical Complex (ECC), located near Aveiro, in the center region of Portugal, has had intense industrial activity since the early 1950s, and high environmental levels of potentially toxic elements such as arsenic (As) and mercury (Hg) have been reported at this region [32,33]. Despite the significant number of studies focusing on determining the severity and the extension of the contamination [34,35,36,37,38] only a few have tried to assess potential health effects on the resident population [39,40,41,42,43]. Hence, the area displays interesting characteristics to study the potential effect of long-term exposures to chemicals in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Recent studies have found negative health effects even aer low dose exposures to this trace element. 11,13 Zinc (Zn) is an essential nutrient and, similarly to Pb, it is ubiquitous in the environment. Although Zn is not involved in cellular redox cycle and has traditionally been regarded as relatively nontoxic, studies increasingly show that Zn 2+ is a potent killer of neurons, glia, and other cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Adenocarcinoma gastric human cells (AGS) have successfully been used as a model to study the cyto- and genotoxicity of environmental mixtures to which children may be exposed by ingestion. As a matter of fact, nanoparticles and bioaccessible fractions of settled dust have been previously studied on this cell type [ 40 , 41 ]. Therefore, they were considered a relevant model for this study.…”
Section: Introductionmentioning
confidence: 99%